2001
DOI: 10.1001/archinte.161.21.2564
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Presence of Varices in Cirrhotic Patients Without a History of Variceal Hemorrhage

Abstract: Low platelet count and advanced Child-Pugh class were associated with the presence of any varices and with large varices. These factors allow identification of a subgroup of cirrhotic patients who would benefit most from referral for endoscopic screening for varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 32 publications
14
110
1
3
Order By: Relevance
“…It may be explained according to the issue that palpable spleen as well as LEV may both be related to the presence of a higher portal pressure. Different factors found to be important for this purpose included splenomegaly [23][24][25][26][27][28] , thrombocytopenia [23][24][25][26][27][28][29][30] , ascites [25,27] , hepatic encephalopathy [25] , serum albumin concentration [30] , serum bilirubin levels [30] , and Child-Pugh score [27,28] . Thus, the results of our study are consistent with those of the previously published data.…”
Section: Resultsmentioning
confidence: 99%
“…It may be explained according to the issue that palpable spleen as well as LEV may both be related to the presence of a higher portal pressure. Different factors found to be important for this purpose included splenomegaly [23][24][25][26][27][28] , thrombocytopenia [23][24][25][26][27][28][29][30] , ascites [25,27] , hepatic encephalopathy [25] , serum albumin concentration [30] , serum bilirubin levels [30] , and Child-Pugh score [27,28] . Thus, the results of our study are consistent with those of the previously published data.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the presence of splenomegaly in cirrhotic patients is likely the result of vascular disturbance that are mainly linked to portal hypertension. 2,4 In our study, it was observed that mean platelet count in grade-I EV was 142568.42±6640.369/mm 3 3 . Platelet count showed a highly statistical significant inverse correlation with the grading of esophageal varices, which is in agreement with Thomopulos et al 5 Esophageal varices were graded according to Paquet 6 .…”
Section: Fig-2mentioning
confidence: 51%
“…Table 3 summarizes the findings from 3 identified peer-reviewed studies that identify risk factors for underlying esophageal varices in cirrhosis. [5][6][7] All 3 studies identify thrombocytopenia as a significant risk factor for underlying varices, with an odds ratio ranging from 1.7 to 2.8 versus patients with normal platelet counts. The presence of splenomegaly detected on physical examination has an odds ratio of 2.0, 5 and the presence of a portal vein size greater than 13 mm on ultrasonography has an odds ratio of 2.9.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients with either a platelet count less than 88,000/mL, a prothrombin time activity less than 70%, a portal vein diameter greater than 13 mm, or splenomegaly are considered to be at high risk for varices. [5][6][7] High-risk patients receive screening endoscopy and are placed on BB therapy if moderate or large varices are found, whereas low-risk patients are followed clinically without prophylactic therapy. High-risk patients found to have small or no varices on screening endoscopy also do not receive prophylactic therapy but subsequently undergo repeat screening endoscopy every other year.…”
Section: Decision Modelmentioning
confidence: 99%
See 1 more Smart Citation